Calprotectin and Calgranulin C as Biomarkers of Pancreatic Tumors: Baseline Levels and Level Changes after Surgery. (9th September 2019) - Holub, Michal; Bartáková, Eva; Stráníková, Alžběta; Koblihová, Eva; Arientová, Simona; Blahutová, Marie; Máca, Jan; Ryska, Miroslav
Abstract : Pancreatic tumors and their surgical resection are associated with significant morbidity and mortality, and the biomarkers currently used for these conditions have limited sensitivity and specificity. Because calprotectin and calgranulin C serum levels have been demonstrated to be potential biomarkers of certain cancers and complications of major surgery, the levels of both proteins were tested in the current study in patients with benign and malignant pancreatic tumors that were surgically removed. The baseline serum levels and kinetics of calprotectin and calgranulin C during the 7-day postoperative period were evaluated with immunoassays in 98 adult patients who underwent pancreatic surgery. The baseline serum levels of calprotectin and calgranulin C in patients with malignant (n = 84 ) and benign tumors (n = 14 ) were significantly higher (p < 0.01 ) when compared to those in the healthy controls (n = 26 ). The serum levels of both proteins were also significantly (p < 0.05 ) higher in patients with benign tumors than in those with malignant tumors. After surgery, the serum levels of calprotectin and calgranulin C were significantly (p < 0.01 ) higher than their baseline values, and this elevation persisted throughout the seven days of the follow-up period. Interestingly, starting on day 1 of the postoperative period, the serum levels of both proteins were significantly (p < 0.05 ) higher in the 37 patients who developed postoperative pancreatic fistulas (POPFs) than in the patients who had uneventful recoveries (n = 61 ). Moreover, the serum levels of calprotectin and calgranulin C demonstrated a significant predictive value for the development of POPF; the predictive values of these two proteins were better than those of the serum level of C-reactive protein and the white blood cell count. Taken together, the results of this study suggest that calprotectin and calgranulin C serum levels are potential biomarkers for pancreatic tumors, surgical injury to the pancreatic tissue and the development of POPFs.